PENYULUHAN POLA PIKIR WAWASAN KRISTEN TENTANG LGBT PADA MAHASISWA JURUSAN PENDIDIKAN IPS UNIVERSITAS PELITA HARAPAN DAN GURU SD GMIM LELEMA KABUPATEN MINAHASA SELATAN - Walukow, Devy Stany; Silitonga, Roedy (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The ease of obtaining information about LGBT and becoming a ‘lifestyle’ of some people today, has raised concerns in the world of education. The understanding of gender in the name of human rights can open space for the formation of LGBT in Indonesia. This condition destroys the human concept of God's creation, which is differentiated between men and women. However, LGBT people as individuals created by God, and have fallen into sin, should not receive inhumane treatment. LGBT people need to be given a touch of ‘love’ in the form of education to bring LGBT people to the construction of God's creation. This concept needs to be understood by social science education teachers of Universitas Pelita Harapan and teachers of Elementary School of GMIM Lelema in South Minahasa Regency as the bearers of character building. It turns out that LGBT is associated with the concept of gender and has not been properly understood. The variety of gender thinking in the social sciences about gender requires direction from Christian insights. Activities were carried out in the form of virtual face-to-face through zoom and Pre-Test and Post-Test were conducted.